2023
DOI: 10.1002/ppp3.10402
|View full text |Cite
|
Sign up to set email alerts
|

What can hippopotamus isotopes tell us about past distributions of C4 grassy biomes on Madagascar?

Abstract: Societal Impact StatementToday, expansive C4 grassy biomes exist across central, western, and northern Madagascar. Some researchers have argued that the island's now‐extinct pygmy hippopotamuses belonged to a megaherbivore grazing guild that maintained these grasslands prior to human arrival. However, the chemistry of hippo bones indicates that C4 grasses were only a minor part of hippo diet. This, in turn, suggests that C4 grasses were present but not widespread when hippos were alive and that grasses expande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…Recent findings discount Malagasy hippopotamus (Crowley et al, 2023) and elephant birds (Hansford & Turvey, 2022), but Aldabrachelys may represent just such a grazer. Present-day Madagascar is largely grassland with limited mosaics of closed-canopy dry forest and open-canopy tapia woodlands, across the historic range of Aldabrachelys.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recent findings discount Malagasy hippopotamus (Crowley et al, 2023) and elephant birds (Hansford & Turvey, 2022), but Aldabrachelys may represent just such a grazer. Present-day Madagascar is largely grassland with limited mosaics of closed-canopy dry forest and open-canopy tapia woodlands, across the historic range of Aldabrachelys.…”
Section: Introductionmentioning
confidence: 94%
“…If the first hypothesis were correct, extinct Malagasy hippos would have fed in open grasslands dominated by C 4 grasses (and have higher δ 13 C values), and browsing of C 3 woody vegetation in woodland and forested habitats would have been uncommon and atypical. Isotope data now clearly find that Malagasy hippos were mostly C 3 feeders, never predominant grazers, lived mostly in forest and browsed in moist and wooded habitats, even in regions that today are vast grasslands (Crowley et al, 2023), corroborating earlier studies that showed there never were pure C 4 grazing hippos (Crowley et al, 2021;Godfrey & Crowley, 2016;Hansford & Turvey, 2022;Joseph et al, 2024a). As Madagascar's hippos lived predominantly in forests and wetlands, their feeding strategy has been identified by various authors as similar to that of forest-limited African pygmy hippopotamus, Choeropsis liberiensis (Crowley et al, 2023;Hansford & Turvey, 2022), which does not form obligate C 4 grazing lawns .…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests large scale tree-loss has likely already taken place across much of the vast treeless grasslands (Crowley et al, 2023;, and because transformation transpired ca. 1000 CE, this landscape-scale historic deforestation does not reflect when evaluation considers only current tree-loss.…”
Section: Madagascar's Grasslands Share Map and Relic Habitat With Afr...mentioning
confidence: 99%
“…This lens is important, because palaeoecological evidence suggests that much of Malagasy tree-loss has already occurred and that large aspects of Madagascar's treeless grasslands may be fire-induced anthropogenic formations that formed ca. 1000 CE (Burns et al, 2016;Crowley et al, 2023;Godfrey et al, 2019;Hixon et al, 2021;Joseph & Seymour, 2022b;Razafimanantsoa, 2021).…”
Section: Madagascar's Grasslands Share Map and Relic Habitat With Afr...mentioning
confidence: 99%
See 1 more Smart Citation